Major-element and Li, Be compositional evolution of tourmaline in an S-type granite-pegmatite system and its country rocks: an example from Ikaria, Aegean Sea, Greece - Hezel, Dominik; Kalt, Angelika; Marschall, Horst; Ludwig, Thomas; Meyer, Hans-Peter (The Canadian mineralogist, 2011)
The chemical evolution of tourmaline in a granite - pegmatite - hydrothermal system and its metamorphic country-rock on the island of Ikaria, in Greece, has been investigated to elucidate the range of compositions generated from a single intrusive system, and the relation between genetic types of tourmaline and their chemical composition. On Ikaria, an S-type granite intruded metapelites, and several aplitic and pegmatitic dykes originating from the granite cross-cut the granite as well as the country rock. Quartz-tourmaline rocks occur in both the S-type granite and in the metapelite. Tourmaline in rocks genetically related to the granite have Li concentrations between 9.3 and 473 μg/g and Be concentrations between 1.5 and 41.8 μg/g. Tourmaline in rocks genetically related to the metapelite have more than an order of magnitude lower concentrations (Li: 2.0-5.8 μg/g, Be: 0.3-0.9 μg/g). Tourmaline in these rocks is typically zoned, with abrupt changes in composition between core and rim. Generally, the cores have a high Al and low minor-element concentrations. Oscillatory-zoned tourmaline rims formed by diffusion-limited growth. Dykes in which the magma travelled far through the metapelitic country-rocks are more differentiated than others, and contain tourmaline with very low Mg/Fe in the core. The dykes interacted with the surrounding rocks in places, leading to Mg enrichment in the dykes. This interaction also introduced Mn into the dykes; spessartine-rich garnet formed with Li concentrations as high as 166 μg/g. Boron-rich fluids segregating from the metapelite during an amphibolite-facies metamorphic event produced quartz-tourmaline rocks in the metapelite, which are probably unrelated to the S-type granite. The metamorphic fluids in the metapelites interacted with marble units where they were in close vicinity, leading to the formation of Ca-rich tourmaline in those quartz-tourmaline rocks. Concentrations of Li, Be and B in associated minerals decrease as follows: Li: St > Bt > Ms > Grt > Tur, Kfs > Pl; Be: St > Pl > Ms > Tur > Bt > Kfs > Grt; B: Tur >> Ms > Bt > Pl > Grt > Kfs, St.